Analysis of Pressure Drop in Clean Water Piping Installation Using Revit Software - Soibatul Aslamia; Deni Haryadi; Komarudin Komarudin (Sultan Publisher, 2025)
Clean water piping systems in industrial facilities must be designed to ensure adequate residual pressure at all outlets while minimizing energy losses. One critical factor influencing system performance is pressure drop, which results from both friction in straight pipes and localized losses in fittings, valves, and other components. This study analyzes the pressure drop in the clean water distribution network of PT XYZ, Kendal Industrial Estate, using two approaches: manual calculation based on the Darcy–Weisbach equation with total loss coefficients, and simulation using Autodesk Revit’s Pressure Loss Report tool. The manual calculation yielded a total pressure drop of 2.30 bar (≈ 23.0 mH₂O) along the critical path, with approximately 72% of the loss originating from fittings and 28% from pipe wall friction. The Revit simulation produced a total pressure drop of 2.10 bar (≈ 21.4 mH₂O) for the same route, resulting in a deviation of 8.7%, which is within the accepted tolerance of ±10% for BIM-based hydraulic validation. The results demonstrate that Revit can reliably model hydraulic performance when accurate material, dimension, and fixture data are provided. The findings emphasize that optimization strategies should focus on reducing localized losses by minimizing fittings, improving pipe routing, and increasing branch diameters in high-velocity sections. These measures can enhance residual pressure, improve system efficiency, and reduce pump energy requirements. The study validates the use of Autodesk Revit as an effective tool for preliminary hydraulic analysis in compliance with SNI 03-6481-2000, while confirming the importance of manual validation during the design process.